Challenges of Health Information Systems in Indonesia - Rida Hutabarat (Journal Health of Indonesian, 2025)
Health Information System (HIS) is one of the strategic components in national health development because it provides accurate data and information to support the management process, decision-making, and evaluation of health programs. This study aims to identify challenges, principles, and strategies for strengthening HIS in Indonesia. The method used is a qualitative descriptive approach through a literature study of government policies, regulations, and scientific literature related to HIS. The results of the study indicate that the implementation of HIS still faces various obstacles, such as a fragmented system, limited technological infrastructure, low human resource capacity, and a suboptimal data use culture. In addition, strategic issues also include weak legal basis, inter-institutional coordination, and lack of support in terms of funding and capacity development. To overcome these problems, strengthening HIS must be carried out through the use of information and communication technology (ICT), system integration, data standardization, and active involvement of the central and regional governments in system governance. The preparation of a roadmap for strengthening HIS is a concrete step to encourage work efficiency, transparency, and the availability of reliable information in supporting health development in Indonesia.